(untitled) (Proceedings of International Educators Conference, 2024)
This article provides information about the concepts of fact, factoid and fake in Web journalism. Leaders of many countries are trying to use blogs as an effective tool so that they don’t lose their activity in mass media. It’s really good. But it should not be forgotten that information becomes a dangerous tool in the hands of malicious people. If this factor is not given special attention, it will become increasingly stronger. As a result, social networks become the main weapon in the hands of some forces.